Influence of Tawhidic Paradigm in the Training and Development Practices of Islamic Universities - Suhaimi Mhd Sarif; Yusof Ismail; Fuad Muhammad Zein; Yayan Firmansah (Universitas Darussalam Gontor, 2024)
Training and development practices are influenced by organizational direction and environmental dynamism. The organisational bottom line has been the main driver shaping these practices. For Islamic universities, they are influenced by the Tawhidic paradigm. This research aims to explore the influence of the Tawhidic paradigm on Islamic universities’ training and development practices. The study employed qualitative research through personal interviews with staff members of Islamic universities. The Tawhidic paradigm influences training and development at Islamic universities based on the principles of ukhuwwah (brotherhood), ‘adl (justice), and ihsan (benevolence). These principles led to a supportive and cooperative work environment, encourage fair treatment and justice, and inspire individuals to go beyond their basic duties with compassion and benevolence. Furthermore, training and development also align with the Madani Malaysia principles of keMampanan (sustainability), kesejAhteraan (prosperity), Daya cipta (innovation), hormAt (respect), keyakiNan (trust), and Ihsan (compassion).The theoretical contribution enhances understanding of how the Tawhidic paradigm impacts training and development practices, emphasizing ukhuwwah, ‘adl, and ihsan with Madani Malaysia principles in ethical work environments. For policy implications, there is a need for policies that integrate the Tawhidic paradigm into staff training and development, ensuring ongoing training and adaptability. In terms of practical implications, this research guides practitioners in incorporating Tawhidic principles into training, fostering collaboration, fairness, and compassion, and aligning with Madani Malaysia values.